2018
DOI: 10.3389/fphar.2018.00723
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Nanomaterials Encapsulating Angelica gigas Nakai Extract for Potential Anticancer Nanomedicine

Abstract: We prepared hybrids consisting of Angelica gigas Nakai (AGN) root or flower extract and layered double hydroxide (LDH) for potential anticancer nanomedicine, as decursin species (DS) in AGN are known to have anticancer activity. Dimethylsulfoxide solvent was determined hybridization reaction media, as it has affinity to both AGN and LDH moiety. In order to develop inter-particle spaces in LDH, a reversible dehydration-rehydration, so-called reconstruction route, was applied in AGN-LDH hybridization. Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…As zeta-potential of ZOE–LDH still resided in the positive region, it suggested that ZOE was encapsulated in the interparticle space of LDH, rather than attached on the surface of LDH. This result was similar to our previous result that Angelica gigas Nakai extract incorporated in LDH hybrid showed positive zeta-potential [43]. Based on XRD patterns, IR spectra, SEM images, and zeta-potential, we could conclude that MgFe–LDH lost its lamellar structure upon calcination, and the original layered structure was partially recovered to develop the interparticle space of LDH with intact ZOE moiety.…”
Section: Resultssupporting
confidence: 90%
“…As zeta-potential of ZOE–LDH still resided in the positive region, it suggested that ZOE was encapsulated in the interparticle space of LDH, rather than attached on the surface of LDH. This result was similar to our previous result that Angelica gigas Nakai extract incorporated in LDH hybrid showed positive zeta-potential [43]. Based on XRD patterns, IR spectra, SEM images, and zeta-potential, we could conclude that MgFe–LDH lost its lamellar structure upon calcination, and the original layered structure was partially recovered to develop the interparticle space of LDH with intact ZOE moiety.…”
Section: Resultssupporting
confidence: 90%
“…It was worthy to note that the GML-R hybrid, completely different from GML-I, showed house-of-cards like structure (Figure 2d), suggesting that particle thickness of LDH becomes thinner and that the layers were randomly stacked with GM moiety. This morphology tends to have inter-particle space, which might encapsulate large biomolecules in natural extract as reported previously [28]. We could observe a few LDO-like particles in the SEM image of GML-R which corresponded to the XRD result.…”
Section: Resultssupporting
confidence: 85%
“…The severe crystallinity change is thought to be due to large molecular dimension of GM moiety. In our previous report, incorporation of Angelica gigas Nakai natural extract into LDH through reconstruction significantly reduced crystallinity of LDH due to perturbed stacking of LDH layers by the steric hindrance of large organic species in natural extract [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations